2021
DOI: 10.1371/journal.pntd.0009612
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants associated with Zika virus infection in pregnant women

Abstract: This study aims to describe the sociodemographic determinants associated with exposure to Zika Virus (ZIKV) in pregnant women during the 2015–2016 epidemic in Salvador, Brazil. Methods We recruited women who gave birth between October 2015 and January 2016 to a cross-sectional study at a referral maternity hospital in Salvador, Brazil. We collected information on their demographic, socioeconomic, and clinical characteristics, and evaluated their ZIKV exposure using a plaque reduction neutralization test. Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Another ecological study also conducted in Recife found microcephaly cases were up to 5.6 times more prevalent in districts of low socioeconomic status than those of high socioeconomic status 17. Similarly, a cross-sectional hospital-based study in Salvador, Bahia state, found that lower education and food insecurity were associated with ZIKV exposure among pregnant persons 11. In the Southeast region of Brazil, a prospective cohort study of ZIKV during pregnancy in Rio de Janeiro also found higher risks of microcephaly among children born to families with lower household income, lower maternal education, and greater household crowding 43.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Another ecological study also conducted in Recife found microcephaly cases were up to 5.6 times more prevalent in districts of low socioeconomic status than those of high socioeconomic status 17. Similarly, a cross-sectional hospital-based study in Salvador, Bahia state, found that lower education and food insecurity were associated with ZIKV exposure among pregnant persons 11. In the Southeast region of Brazil, a prospective cohort study of ZIKV during pregnancy in Rio de Janeiro also found higher risks of microcephaly among children born to families with lower household income, lower maternal education, and greater household crowding 43.…”
Section: Discussionmentioning
confidence: 92%
“… 17 Similarly, a cross-sectional hospital-based study in Salvador, Bahia state, found that lower education and food insecurity were associated with ZIKV exposure among pregnant persons. 11 In the Southeast region of Brazil, a prospective cohort study of ZIKV during pregnancy in Rio de Janeiro also found higher risks of microcephaly among children born to families with lower household income, lower maternal education, and greater household crowding. 43 Conversely, a small case-control study of mothers exposed to ZIKV during pregnancy in Rio de Janeiro found no differences in CZS risk according to the income of the mothers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears more likely that the large number of babies born with birth defects in Brazil is due to high numbers of ZIKV infections among pregnancies in Brazil, not to a higher risk of birth defects. The higher number of ZIKV‐infected pregnancies might be related to socioeconomic conditions (including lower education rate and food insecurity; Nery Jr. et al, 2021), as well as barriers to health services, inadequate sanitation, and poor water supply (Morgan et al, 2021). In addition, countries with transmission starting after recognition of the association between ZIKV and birth defects could better advise pregnant persons on ways to avoid ZIKV transmission.…”
Section: Reasons Why Teratogenic Effects Of Zika Virus Might Have Bee...mentioning
confidence: 99%